Fear of Missing Out (FoMO) and Consumer Behavior in the Digital Era: A PRISMA Systematic Review - Alvita, Meilisa (Dinasti Publisher, 2025)
This study synthesizes five empirical investigations on Fear of Missing Out (FoMO) across different digital consumer contexts. The research objects include consumer purchases in the metaverse, tourism experience sharing on social media, influencer-driven purchase intentions, online learning among university students, and SMEs’ marketing performance. The main objective is to explore how FoMO shapes decision-making, social interaction, academic well-being, and marketing outcomes. The studies employed quantitative survey-based designs with diverse samples from Europe, South America, Asia, and Africa, analyzed using clustering, non-parametric tests, and structural equation modeling. The results consistently show that FoMO drives impulsive buying, intensifies digital self-presentation, mediates the effect of influencers on purchase intention, contributes to academic burnout, and strengthens the impact of social media advertising on business performance. Overall, FoMO emerges as a critical factor in understanding consumer behavior and digital marketing strategies across global contexts